Isolation, screening, and characterisation of flocculating and pectinase producing Kluyveromyces strains - Pereira, Martinha (1999)
Eleven strains of Kluyveromyces marxianus were studied to select the best producers of extracellular endo-polygalacturonase (endo-PG), using glucose and lactose as carbon source. Flocculation ability was also assayed. Four out of eleven strains produced more enzyme when glucose was used as substrate. Only one strain was a better endo-PG producer when lactose was used as carbon source, although producing less enzyme than the best performing strain grown on lactose. The best enzyme production was obtained for strain K. marxianus CH4-1 when grown on glucose. In all cases, as a consequence of a lower rate of substrate consumption, enzyme productivity was between two- and three-fold lower when yeasts were grown on lactose. It was also shown that all strains formed flocs only when grown on lactose; on glucose the cells remained powdery.